Analysis of Planning for Clean Water Needs at Grand Sagara West Surabaya Hotel With the Green Buillding Concept - Ali Rafsanjani, Sofyan; Rooslan Santosa, F Edy; Durrotun Nasihien, Ronny (International Journal of Engineering, Science and Information Technology, 2021)
Water is the basic necessity of every living thing on earth. Humans depend on water not only for meeting domestic household needs but also for needs such as production needs, industrial needs and other needs. The need for clean water is the amount of water that will be used fairly for basic human needs (domestic) and other activities that require water. The hospitality industry is a commercially managed business. This study aims to determine the impact of the use of clean water that occurs during the construction and operation of the Grand Sagara West Surabaya Hotel on Tambak Wedi Village in the next 10 years. The need for clean water for Tambak Wedi Village in 2019 prior to the construction and operation of the Grand Sagara West Surabaya Hotel is 0.0566 m³ / sec, whereas after construction and operation in 2029 is 0.1118 m³ / sec. So, the amount of clean water discharge in Tambak Wedi Urban Village that must be fulfilled by the PDAM in Surabaya in 2029 is 0.0288 m³ / sec. Clean water, water needs, water discharge, hotel, PDAM Surabaya city.